A modern assessment of students in schools in the education system of Kazakhstan - Iskakova, R.K.; Azhigenova, S.K.; Zengin, Zh. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
In this article is about a new system of assessment in Kazakhstan schools, it is proved that it is an important part of the learning that allows you to define the causes of learning and non-learning. The modern assessment system, based on the new programs, provides for the assessment of knowledge as a result of the formative, summative criteria-based assessment of classroom learning in accordance with the types of tasks in the teaching and its learning outcomes. The assessment system has also undergone radical changes and has been analyzed in a system of criteria-based assessment, with a clear set of predictive criteria for students' progress and consistency, consistency and effectiveness. The importance of understanding the depth of knowledge, skills and flexibility in evaluating the students' knowledge is emphasized. The new assessment system has come to the conclusion that it is possible to improve the educational society of teaching, to create the moral and spiritual qualities of the student, to comply with the content of the sections and the timing of the proposed topics, to focus on social skills, and to actively participate in the learning process.
Қазақстан білім беру жүйесіндегі мектеп оқушыларын жаңаша бағалау мəселесі
Новая система оценивания школьников в системе образования Казахстана
Keywords: assessment; quality; Criteria-based assessment; summative assessment; self-assessment; knowledge; skills; taxonomy; effective results; educational process; develop criteria; formulate assessment; learning; curriculum; evaluate